Designing Posters of Palembang’s Culinary Specialties as a Medium for Education on History and Local Cultural Identity - Prasetya, Adi; Mujiyono (Universitas Negeri Semarang, 2025)
Traditional cuisine plays an important role in strengthening history and cultural values for public awareness, especially amidst the tide of globalization that erodes local cultural identities. The design of posters featuring traditional Palembang cuisine as a medium for historical education to visually and informatively introduce its diversity to the younger generation. Typical Palembang cuisine such as pempek, tekwan, model, lenggang, laksan, and burgo not only serves as a consumption necessity but also represents the acculturation of Sriwijaya, Malay, and Chinese cultures. The method used in designing the Palembang culinary poster is the design thinking approach, which consists of five stages: empathize, define, ideate, prototype, and test. Data was obtained through observation, interviews, questionnaire distribution, and literature study. The results show that the posters designed with a contextual visual and narrative approach can serve as a communicative and meaningful non-formal educational tool. The poster features local visual elements, such as the traditional Palembang songket fabric motifs, the Ampera Bridge, local cultural tourist destinations, and is disseminated through social media to reach a wide audience. These findings indicate that visual media are not only effective in introducing the diverse culinary offerings of Palembang but can also strengthen cultural identity and continuously preserve intangible cultural heritage.